Hubungan Serapan N, P, dan K Tanaman Cabai terhadap Residunya di dalam Tanah yang Diberi Pupuk Cair Organik dengan NPK - Eso Solihin; Rija Sudirja; Maya Damayani; Nadia Nuraniya Kamaludin (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACTThe Relationship between N, P, and K Uptake of Chili Plants to Their Residues in Soil Treated by Liquid Organic Fertilizers and NPKThis study aims to determine the relationship of N, P, and K uptake of chili plants towards the residues in the soil treated with liquid organic fertilizer with the addition of inorganic fertilizers of N, P and K. The research was conducted from September 2017 to January 2018 in the experimental field and KTNT Laboratory, Faculty of Agriculture, Universitas Padjadjaran. The design used was simple complete randomized design with 10 treatments and were repeated 3 times, with the treatment arrangement as follows: A = Control 0 PS + 0 NPK, B = 0 PCO + 1 NPK, C = 1 PCO + 0 NPK, D = 1 PCO + ¼ NPK, E = 1 PCO + ½ NPK, F = 1 PCO + ¾ NPK, G = 1 PCO + 1 NPK, H = ¼ PCO + ¾ NPK, I = ½ PCO + ¾ NPK and J = ¾ PCO + ¾ NPK. The results showed that the highest nutrient uptake and residue was found in the treatment of 1 PCO + ¾ NPK. Relationship between N, P and K uptake with nutrient residue on the soil was detected. The N, P and K residues were influenced by the N, P and K uptake of chili plants of 92%, 98%, and 97%, respectively.Keywords: Chili, NPK, Liquid Organic Fertilizer, Residue, AbsorptionABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan serapan N, P, dan K tanaman cabai terhadap residunya di dalam tanah yang diberi pupuk cair organik dengan pupuk anorganik N, P dan K. Penelitian dilaksanakan pada bulan September 2017 sampai dengan Januari 2018 di kebun percobaan dan Laboratorium KTNT Fakultas Pertanian, Universitas Padjadjaran. Rancangan yang digunakan adalah RAK sederhana dengan 10 perlakuan yang diulang 3 kali dengan susunan perlakuan sebagai berikut: A = Kontrol 0 PS + 0 NPK, B = 0 PCO + 1 NPK, C = 1 PCO + 0 NPK, D = 1 PCO + ¼ NPK, E = 1 PCO + ½ NPK, F = 1 PCO + ¾ NPK, G= 1 PCO + 1 NPK, H = ¼ PCO + ¾ NPK, I = ½ CO + ¾ PK dan J = ¾ PCO + ¾ NPK. Hasil penelitian menunjukkan bahwa serapan dan residu hara tertinggi ialah perlakuan F = 1 PCO + ¾ NPK. Terdapat hubungan antara serapan N, P dan K dengan residu hara pada tanah. Residu N, P dan K dipengaruhi oleh serapan N, P dan K tanaman cabai masing-masing sebesar 92% serapan N, 98% serapan P, dan 97% serapan K.Kata Kunci: Cabai, NPK, PCO, Residu, Serapan